Encyclopedia of quantitative finance - Cont, Rama; Tankov, Peter (Wiley, 2010)
* A multi-volume major reference work, presenting a timely and comprehensive body of knowledge designed to serve as an essential reference for the finance community. * Includes contributions from leading figures in industry and academic research and provides an authoritative exposition of quantitative finance